Radio footprints of a minor merger in the Shapley Supercluster: from supercluster down to galactic scales - Venturi, T; Giacintucci, S; Merluzzi, P; Bardelli, S; Busarello, G; Dallacasa, D; Sikhosana, SP; Marvil, J; Smirnov, O; Bourdin, H; Mazzotta, P; Rossetti, M; et al. (EDP Sciences, 2022)
Context. The Shapley Supercluster (äzaa 0.048) contains several tens of gravitationally bound clusters and groups, making it an ideal subject for radio studies of cluster mergers. Aims. We used new high sensitivity radio observations to investigate the less energetic events of mass assembly in the Shapley Supercluster from supercluster down to galactic scales. Methods. We created total intensity images of the full region between A3558 and A3562, from a 14;230 to a 14;1650 MHz, using ASKAP, MeerKAT and the GMRT, with sensitivities ranging from a 14;6 to a 14;100 μJy beama 1. We performed a detailed morphological and spectral study of the extended emission features, complemented with ESO-VST optical imaging and X-ray data from XMM-Newton. Results. We report the first GHz frequency detection of extremely low brightness intercluster diffuse emission on a a 14;1 Mpc scale connecting a cluster and a group, namely: A3562 and the group SC 1329a 313. It is morphologically similar to the X-ray emission in the region. We also found (1) a radio tail generated by ram pressure stripping in the galaxy SOS 61086 in SC 1329a 313; (2) a head-tail radio galaxy, whose tail is broken and culminates in a misaligned bar; (3) ultrasteep diffuse emission at the centre of A3558. Finally (4), we confirm the ultra-steep spectrum nature of the radio halo in A3562. Conclusions. Our study strongly supports the scenario of a flyby of SC 1329a 313 north of A3562 into the supercluster core. This event perturbed the centre of A3562, leaving traces of this interaction in the form of turbulence between A3562 and SC 1329a 313, at the origin of the radio bridge and eventually affecting the evolution of individual supercluster galaxies by triggering ram pressure stripping. Our work shows that minor mergers can be spectacular and have the potential to generate diffuse radio emission that carries important information on the formation of large-scale structures in the Universe.